Islamic Religious Understanding in Forming the Mentality of the Indonesian Army at Kodim 1802/Sorong - Triyana, Triyana; Dahlan, Moh.; Hasbullah, Kun; Haramain, Fathur Baldan (Jurnal Adabiyah, 2024)
This research aims to explore the Islamic Religious Understanding program in shaping the mentality of the Indonesian Army at Kodim 1802/Sorong. The research method used is field research with a case study approach. In this approach, researchers analyze selected cases in depth to gain a comprehensive understanding of the phenomenon or problem being researched from various perspectives. Data was collected through the research findings based on the programs implemented at Kodim 1802/Sorong, which were then analyzed qualitatively. The results of this research show that the Islamic Religious Understanding implemented at Kodim 1802 Sorong can gradually shape the mentality of the soldiers. However, there are challenges in implementing the program, including a lack of role models from leaders, a gap between coaching materials and field realities, and a lack of planning that is in accordance with educational theory. The suggested solutions include more critical learning about faith and morals, separating mental and ideological development, using interesting learning methods, and improving lesson structures to increase understanding and participation of TNI AD members on an ongoing basis. Therefore this research provides an important contribution in developing a more effective mental development program in the Kodim 1802/Sorong environment, as well as providing direction for further research and development in this field. Abtsrak Penelitian ini bertujuan untuk mengeksplorasi program Pendidikan Agama Islam dalam membentuk mental TNI AD di Kodim 1802/Sorong. Metode penelitian yang digunakan yakni penelitian lapangan dengan pendekatan studi kasus. Dalam pendekatan ini, peneliti menganalisis kasus yang dipilih secara mendalam untuk mendapatkan pemahaman yang komprehensif tentang fenomena atau masalah yang sedang diteliti dari berbagai perspektif. Data dikumpulkan melalui temuan penulis berdasarkan program-program yang diterapkan di Kodim 1802/Sorong, yang kemudian dianalisis secara kualitatif. Hasil penelitian ini menunjukkan bahwa Pendidikan Agama Islam yang diterapkan di Kodim 1802 Sorong dapat membentuk mentalitas para prajurit secara bertahap. Namun, terdapat tantangan dalam mengimplementasikan programnya, termasuk kurangnya teladan dari pimpinan, kesenjangan antara materi pembinaan dengan realitas lapangan, dan kurangnya perencanaan yang sesuai dengan teori pendidikan. Solusi yang disarankan meliputi pembelajaran yang lebih kritis tentang akidah dan akhlak, pemisahan antara pembinaan mental dan ideologi, penggunaan metode pembelajaran yang menarik, dan peningkatan struktur pelajaran untuk meningkatkan pemahaman dan partisipasi anggota TNI AD secara berkesinambungan. Penelitian ini berkontribusi penting dalam mengembangkan program pembinaan mental yang lebih efektif di lingkungan Kodim 1802/Sorong, serta memberikan arahan bagi penelitian dan pengembangan selanjutnya dalam bidang ini.